Research on the Coupled Modulation Transfer Function of the Discrete Sampling System with Hexagonal Fiber-Optic Imaging Bundles - Wenxian Li; Chengshan Han; Congjun Wu; Yawei Huang; Hang Zhang (Applied Sciences, 2022)
In this study, we developed a numerical model of the coupled modulation transfer function (coupled-MTF) based on the discrete sampling system from the perspective of optical system imaging quality evaluation for coupled two-dimensional discrete sampling characteristics of the hexagonally aligned fiber-optic imaging bundles and CCD image elements. The results show that when the spatial frequency of the input target signal deviates from the Nyquist frequency by 1%, an increase in the number of fibers leads to a faster convergence of the oscillation of the coupled-MTF, and the coupled-MTF converges to a stable value when the number of fibers reaches 1000 × 1000. The deviation of the spatial frequency of the input target signal from the Nyquist frequency is within 1%, and the oscillatory convergence of the coupled-MTF accelerates with increasing deviation. The coupled-MTF oscillates with the deviation period of the wave peak of the input target signal from the initial position of the fiber center, and the theoretical oscillation spatial period is twice the fiber diameter. This study produces important guidelines for the selection of the number of fibers, input spatial frequency, and initial position deviation of the hexagonally arranged fiber imaging bundles.